Health-related quality of life questionnaires in lung cancer trials: A systematic literature review - Kathrin Damm; Nicole Roeske; Christian Jacob (Health Economics Review, 2013)
Background: Lung cancer is one of the leading causes of cancer deaths. Treatment goals are the relief of symptoms and the increase of overall survival. With the rising number of treatment alternatives, the need for comparable assessments of health-related quality of life (HRQoL) parameters grows. The aim of this paper was to identify and describe measurement instruments applied in lung cancer patients under drug therapy. Methods: We conducted a systematic literature review at the beginning of 2011 using the electronic database Pubmed. Results: A total of 43 studies were included in the review. About 17 different measurement instruments were identified, including 5 generic, 5 cancer-specific, 4 lung cancer-specific and 3 symptom-specific questionnaires. In 29 studies at least 2 instruments were used. In most cases these were cancer and lung cancer-specific ones. The most frequently used instruments are the EORTC QLQ-C30 and its lung cancer modules LC13 or LC17. Only 5 studies combined (lung) cancer-specific questionnaires with generic instruments. Conclusions: The EORTC-C30 and EORTC-LC13 are the most frequently used health-related quality of life measurement instruments in pharmacological lung cancer trials.
Keywords: 330; lung cancer; health-related quality of life; questionnaires; health economics; utility measurement